If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying x^{2}+ -64 = 0 Reorder the terms: -64 + x^{2}= 0 Solving -64 + x^{2}= 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '64' to each side of the equation. -64 + 64 + x^{2}= 0 + 64 Combine like terms: -64 + 64 = 0 0 + x^{2}= 0 + 64 x^{2}= 0 + 64 Combine like terms: 0 + 64 = 64 x^{2}= 64 Simplifying x^{2}= 64 Take the square root of each side: x = {-8, 8}

| r^2-4r-32=0 | | b^2+8b=0 | | n^2+6n+8=0 | | x^2+7x+10=0 | | r^2+7r+12=0 | | m^2-2m-48=0 | | n^2-10n+25=0 | | p^2-7p+12=0 | | k^2+13k+40=0 | | a^2+2a-24=0 | | n^2+15n+56=0 | | v^2+7v-8=0 | | b^2+9b+20=0 | | n^2-11n+24=0 | | x^2-13x+40=0 | | r^2-12r+35=0 | | m^2-5m=0 | | 5x^2=50 | | t^2+7t-35=2t-11 | | 2(x^2)-7x=1 | | x^2+4x-2m=0 | | 27x^2-5x=0 | | 7e^8+t=2 | | 13x^2-28x=0 | | 15n+3n^4-4n+12n^4+n= | | 2x^2-24x=-2x^2-7x-18 | | 30x^3-9x^2-3x=0 | | x^2+4=17 | | (x^3+2x+3x+6)= | | (2x^3+3)= | | (x^2+3)(x^3+2x^2+3x+6)+(2x^3+3)= | | 10y^2+33y+20=0 |

- Equations solver - equations involving one unknown
- Quadratic equations solver
- Percentage Calculator - Step by step
- Derivative calculator - step by step
- Graphs of functions
- Factorization
- Greatest Common Factor
- Least Common Multiple
- System of equations - step by step solver
- Fractions calculator - step by step
- Theory in mathematics
- Roman numerals conversion
- Tip calculator
- Numbers as decimals, fractions, percentages
- More or less than - questions